Civil responsability and environmental inhibitory provision (Research, Society and Development, 2023)
This scientific article discusses the importance of protecting the environment for the benefit of man himself. Demonstrates the need for a balance between environmental protection and economic development, highlighting the importance of managing environmental risks. It presents as a general objective the study of environmental protection, and as specific objectives it studies the institute of environmental responsibility and the environmental inhibitory guardianship. It identifies the injunction as a way of accessing justice able to prevent the occurrence of the offense. It analyzes the legal nature of the injunction and its assumptions. It demonstrates the differentiated nature of environmental damage and its species, which cannot simply be converted into pecuniary. Demonstrates the main differences between the inhibitory provision and the compensatory provision. Outlines aspects of environmental responsibility. Finally, it covers the issue of evidence in the injunction and the criteria for setting a fine as a form of coercion on the defendant.